Clinical utility of Todai OncoPanel in the setting of approved comprehensive cancer genomic profiling tests in Japan. Issue 4 (17th January 2023) - Kage, Hidenori; Shinozaki‐Ushiku, Aya; Ishigaki, Kazunaga; Sato, Yusuke; Tanabe, Masahiko; Tanaka, Shota; Tanikawa, Michihiro; Watanabe, Kousuke; Kato, Shingo; Akagi, Kiwamu; Uchino, Keita; Mitani, Kinuko; et al.
Abstract: Comprehensive cancer genome profiling (CGP) has been nationally reimbursed in Japan since June 2019. Less than 10% of the patients have been reported to undergo recommended treatment. Todai OncoPanel (TOP) is a dual DNA–RNA panel as well as a paired tumor–normal matched test. Two hundred patients underwent TOP as part of Advanced Medical Care B with approval from the Ministry of Health, Labour and Welfare between September 2018 and December 2019. Tests were carried out in patients with cancers without standard treatment or when patients had already undergone standard treatment. Data from DNA and RNA panels were analyzed in 198 and 191 patients, respectively. The percentage of patients who were given therapeutic or diagnostic recommendations was 61% (120/198). One hundred and four samples (53%) harbored gene alterations that were detected with the DNA panel and had potential treatment implications, and 14 samples (7%) had a high tumor mutational burden. Twenty‐two samples (11.1%) harbored 30 fusion transcripts or MET exon 14 skipping that were detected by the RNA panel. Of those 30 transcripts, 6 had treatment implications and 4 had diagnostic implications. Thirteen patients (7%) were found to have pathogenic or likely pathogenic germline variants and genetic counseling was recommended. Overall, 12 patients (6%) received recommended treatment. In summary, patients benefited from both TOP DNA and RNA panels while following the same indication as the approved CGP tests. (UMIN000033647). Abstract : Todai OncoPanel (TOP) is a dual DNA‐RNA panel as well as a paired tumor‐normal matched test. Pharmaceuticals and Medical Devices Agency (PMDA) indications for comprehensive cancer genomic profiling were followed in this study. The percentage of patients who were given therapeutic or diagnostic recommendations was 61%, including patients with fusion or MET exon 14 skipping transcripts that led to recommendations.